2008
DOI: 10.1038/jes.2008.11
|View full text |Cite
|
Sign up to set email alerts
|

Tracking personal exposure to particulate diesel exhaust in a diesel freight terminal using organic tracer analysis

Abstract: Personal exposure to particle-phase molecular markers was measured at a trucking terminal in St Louis, MO, as part of a larger epidemiologic project aimed at assessing carbonaceous fine particulate matter (PM) exposure in this occupational setting. The integration of parallel personal exposure, ambient worksite area and ambient urban background (St Louis Supersite) measurements provided a unique opportunity to track the work-related exposure to carbonaceous fine PM in a freight terminal. The data were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
(40 reference statements)
0
14
0
1
Order By: Relevance
“…5(a) ). However, the presence of hopanes raises the question of whether they come from diesel fuel itself or from engine lubricating oils, as is sometimes assumed (Sheesley et al 2009 ; Huang et al 2013 ). Since these compounds’ molecular weight ranges from 370 to 482 Da, oil fractions used for diesel fuel production (b.p.…”
Section: Resultsmentioning
confidence: 99%
“…5(a) ). However, the presence of hopanes raises the question of whether they come from diesel fuel itself or from engine lubricating oils, as is sometimes assumed (Sheesley et al 2009 ; Huang et al 2013 ). Since these compounds’ molecular weight ranges from 370 to 482 Da, oil fractions used for diesel fuel production (b.p.…”
Section: Resultsmentioning
confidence: 99%
“…Source apportionment data in the LH drivers, P&D drivers, and dockworkers indicated that most (~ 80% or greater) of the EC was from diesel sources with a smaller percentage from spark-ignition vehicles and lubricating oil (Sheesley et al 2008a). OC source apportionment indicated a substantial mobile source contribution that was mostly attributable to lubricating oil.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, average exposure to hopanes, specific tracers of motor vehicle exhaust in our study setting, was significantly higher among women living in the village closest to the highway (median distance = 76 m) compared with those in the village farthest from the highway (median distance = 548 m) (4.6 vs. 1.1 ng/m 3 ; P < 0.001 for both seasons; Table S4). In fact, the average near-highway hopane exposures exceeded occupational levels among US trucking terminal workers (4.6 vs. 1.9 ng/m 3 ) (20).…”
Section: Significancementioning
confidence: 91%